TINJAUAN HUKUM PELEPASAN TANAH ULAYAT - Wijaya, Happy Trizna (Mimbar Keadilan, 2020)
Since September 24, 1960 Law No. 5/1960 was stipulated regarding Basic Regulations on Agrarian Principles or often referred to as the Basic Agrarian Law (UUPA), adopting legal unification and based on customary law. Customary land law is original law, has a unique characteristic, where individual rights to land are personal rights but in it contain togetherness. Land controlled by customary law communities is known as ulayat rights. Although customary law is the basis of the LoGA, problems with ownership rights to customary land often occur due to unclear land boundaries and customary land tenure by the government without any release of land. The results of this study revealed that the procedure for controlling customary land by the local government through the mechanism of land acquisition as stipulated in Permendagri No. 15 of 1975 provides more opportunities for the Government to control land rights, while the owner / holder of land rights has a very weak position because many rights to land are neglected so that it violates the human rights of land rights holders. With the issuance of Presidential Decree No. 55 of 1993 concerning Land Procurement for the Implementation of Development for the Public Interest in lieu of Permendagri No. 15 of 1975, which provides a protection to holders of land rights to be able to defend their rights. This is also the case with Perpres No. 36 of 2005 Jo Perpres No. 65 of 2006 issued as a substitute for Presidential Decree No. 55 of 1993, far more provide protection to the community to defend their rights, while the government is increasingly limited in obtaining land. So Perpres No. 65 of 2006 provides a guarantee of legal certainty to holders of land rights to be able to defend their rights.Sejak 24 September 1960 ditetapkan Undang-undang Nomor 5 Tahun 1960 tentang Peraturan Dasar Pokok-pokok Agraria atau sering disebut Undang-undang Pokok Agraria (UUPA), menganut unifikasi hukum dan berdasarkan hukum adat. Hukum tanah adat merupakan hukum asli, mempunyai sifat yang khas, dimana hak-hak perorangan atas tanah merupakan hak pribadi akan tetapi didalamnya mengandung unsur kebersamaan. Tanah-tanah yang dikuasai oleh masyarakat hukum adat dikenal dengan sebutan hak ulayat. Walaupun hukum adat merupakan dasar dari UUPA tetapi permasalahan terhadap hak kepemilikan atas tanah adat seringkali terjadi karena penentuan batas tanah hak ulayat yang tidak jelas, maupun karena penguasaan hak atas tanah adat oleh pemerintah tanpa ada pelepasan tanah. Hasil penelitian ini mengungkapkan bahwa Prosedur penguasaan tanah ulayat oleh Pemda melalui mekanisme pembebasan tanah yang tertuang dalam Permendagri No. 15 Tahun 1975 lebih memberikan kesempatan kepada pihak Pemerintah untuk menguasai hak atas tanah, sedangkan pemilik/pemegang hak atas tanah mempunyai kedudukan yang sangat lemah karena banyak hak atas tanah yang diabaikan sehingga sangat melanggar hak asasi pemegang hak atas tanah. Dengan diterbitkannya Kepres No. 55 Tahun 1993 mengenai Pengadaan Tanah Bagi Pelaksanaan Pembangunan Untuk Kepentingan Umum sebagai pengganti Permendagri No. 15 Tahun 1975, yang memberikan suatu perlindungan kepada pemegang hak atas tanah untuk dapat mempertahankan haknya. Begitu juga halnya dengan Perpres No. 36 Tahun 2005 Jo Perpres No. 65 Tahun 2006 yang dikeluarkan sebagai pengganti Kepres No. 55 Tahun 1993, jauh lebih memberikan perlindungan kepada pihak masyarakat untuk membela haknya, sedangkan pihak pemerintah semakin terbatas dalam memperoleh tanah. Sehingga Perpres No. 65 Tahun 2006 memberikan suatu jaminan kepastian hukum kepada pemegang hak atas tanah untuk dapat mempertahankan haknya.